Analisis Sentimen Komentar Video Youtube Review Starlink Indonesia oleh Gadgetin menggunakan VADER dan TextBlob - Absharina, Eriene Dheanda; Fatihani Nurqolbiah (The Indonesian Journal of Computer Science, 2025)
Satellite-based internet services such as Starlink have attracted great attention in Indonesia, especially among gadget fans, since their launch six months ago. Public sentiment analysis is necessary to evaluate market acceptance and improve service quality. Objective: This research aims to identify public sentiment towards Starlink Indonesia through analysis of YouTube comments on Starlink Indonesia video reviews by the Gadgetin channel. Methods: With a sentiment analysis approach on a dataset containing 10,591 comments. Using VADER and TextBlob, to classify comments into positive, neutral, and negative sentiment. Conclusion: Analysis obtained with VADER identified 44.7% of comments as neutral, 40.2% positive, and 15.1% negative. Meanwhile, TextBlob shows 50.5% neutral comments, 35.5% positive, and 14% negative.